(untitled) (GEOmedia, 2014)
Italian Fire Brigade is involved in several emergency scenarios, but all this have a common focal point: on field activity. From many years the National Fire fighters has developed on field activity using topographic applications using GIS software, creating a new professional profile. This new high performed operator, highly trained in teorical and practical formation, give a high support to coordination activity in major or multiangency events with specific graphic elaboration. This new operators use specific GIS application mixed with real time radiolocalization equipment, in order to improved the coordination activity. All the aspect concerning training and technological improvement are developed by National Fire fighter officers and operators.